MODEL PENGAMBILAN KEPUTUSAN BERWISATA - Rachmadi, Hari (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
Travelling decision model reflect the Characteristics and type of travel .If diffierenciates and comparcs the tendencies of decison making behaviour in different situational . The Travelling decisaion is established by the different motives of each individuals and group .Where the situational factor affect the bahviour of decison making .Most of the decison making process require the involvement of bahviour in using the information like in the conteporaray decision making.one of the example is the decision to traveling . The logical decision making is the decison made through clear steps that reflects the different characteristcs of behaviour in specifis desicion situations whisc the values are velaved and chesen tourist destination are suitable and desirable